Transcriptome and proteome analysis of steady‐state in a perfusion CHO cell culture process. Issue 8 (7th May 2019) - Bertrand, Vania; Karst, Daniel J.; Bachmann, Alessia; Cantalupo, Katia; Soos, Miroslav; Morbidelli, Massimo
Abstract: Long‐term continuous protein production can be reached by perfusion operation. Through the continuous removal of waste metabolites and supply of nutrients, steady‐state (SS) conditions are achieved after a certain transient period, where the conditions inside the reactor are not only uniform in space but also constant in time. Such stable conditions may have beneficial influences on the reduction of product heterogeneities. In this study, we investigated the impact of perfusion cultivation on the intracellular physiological state of a CHO cell line producing a monoclonal antibody (mAb) by global transcriptomics and proteomics. Despite stable viable cell density was maintained right from the beginning of the cultivation time, productivity decrease, and a transition phase for metabolites and product quality was observed before reaching SS conditions. These were traced back to three sources of transient behaviors being hydrodynamic flow rates, intracellular dynamics of gene expression as well as metabolism and cell line instability, superimposing each other. However, 99.4% of all transcripts and proteins reached SS during the first week or were at SS from the beginning. These results demonstrate that the stable extracellular conditions of perfusion lead to SS also of the cellular level. Abstract : Long‐term continuous protein production can be reached by perfusion operation. Through the continuous removal of waste metabolites and supply of nutrients, intra‐ and extracellular steady‐state (SS) conditions are achieved after a certain transient period, where the conditions inside the reactor are not only uniform in space but also constant in time.